High-stability polylactic acid wave-absorbing fiber and preparation method thereof
The preparation of polylactic acid absorbing fibers by melt spinning method of twin-screw extruder solves the problems of high cost, easy shedding and difficult production of the existing absorbing fiber preparation methods, and achieves high stability, long-lasting absorbing performance and biological Degradability, suitable for mass production and wear comfort needs.
Patent Information
- Application Number
- CN202411098403.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-27
Smart Images

Figure CN119194647A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textiles, and in particular to a high-stability polylactic acid wave-absorbing fiber and a preparation method thereof. Background Art
[0002] With the development of electronic information technology, electromagnetic waves are widely used in various fields, such as military confrontation, aerospace, electronic communications, medical equipment, and household electronic appliances. While bringing convenience to our lives, the harm they cause should not be underestimated. Electromagnetic pollution has become another major source of pollution after water pollution, air pollution, and noise pollution. Anti-electromagnetic pollution has become another important issue in public health care and environmental protection.
[0003] Therefore, the demand for developing electromagnetic wave materials with excellent performance is imminent, especially flexible absorbing composite materials that can be used in the field of smart wearables, which has become a research hotspot in the field of absorbing waves. Absorbing materials not only need to meet the basic requirements of "strong absorbing ability, wide absorbing frequency band, thin thickness, and light weight", but also need to be easy to process, have good flexibility, and meet the requirements of wearable weaving.
[0004] The so-called absorbing material refers to a material that can allow electromagnetic waves radiated to the surface of the material to enter the interior of the material to the greatest extent, and through the interaction between the medium and the electromagnetic waves, convert electromagnetic energy into a series of forms of energy such as internal energy, thereby generating no or minimal electromagnetic wave reflection.
[0005] At present, there are two main ways to prepare absorbing fibers. One is to coat or plate the fibers. Commonly used coating methods include physical vapor deposition, chemical plating, plasma plating, sputtering coating, etc. The absorbing coating usually consists of three parts: absorbent, binder and additive. The processing cycle is long and the cost is high. In addition, the surface coating and plating methods have the disadvantage of easy shedding, poor friction and washing resistance, general durability of absorbing effect, and poor wearing comfort. The second is to design structural absorbing fibers to solve the problem of low addition of absorbing components and achieve the required absorbing range and effect. For example, coaxial spinning is performed using a skin-core spinning assembly, and fibers with a skin-core structure are designed. The absorbing fiber with an absorbent is used as the core layer and is coated with a pure polymer skin layer. This method has high production technology difficulty and low processing efficiency. Summary of the invention
[0006] [Technical issues]
[0007] In view of the defects and shortcomings of the prior art and in order to solve the shortcomings of the prior art, the present invention does not require the use of organic solvents or other sizing equipment, but adopts conventional spinning components and spinnerets to design a simple, environmentally friendly, large-scale production-suitable and economically feasible method for preparing high-stability polylactic acid absorbing fibers. The absorbing fibers not only have stronger and more lasting absorbing properties during use, but are also biodegradable after use.
[0008] [Technical solution]
[0009] The technical concept of the present invention is to propose a method for preparing high-stability polylactic acid absorbing fibers by melt spinning. The method uses polylactic acid as a matrix resin and carbonyl iron powder as an absorbing filler. A twin-screw extruder is used for melt spinning, and the polylactic acid absorbing fibers are obtained through a drawing device.
[0010] In order to achieve the above objectives, the main technical solutions adopted are:
[0011] The first object of the present invention is to provide a method for preparing a polylactic acid absorbing fiber, the method specifically comprising the following steps:
[0012] (1) Mixing raw materials: Weigh polylactic acid particles, carbonyl iron powder and cross-linking agent respectively, and mix them evenly according to the proportion;
[0013] (2) Granulation: The raw materials mixed in step (1) are fed into a granulator, cut into master batches, and the master batches are placed in a vacuum drying oven for drying;
[0014] (3) Melt spinning: The dried masterbatch obtained in step (2) is fed into a twin-screw extruder for melt spinning, and after being stretched by a stretching device and subjected to a collecting device, the polylactic acid absorbing fiber is obtained.
[0015] In one embodiment of the present invention, the polylactic acid particles, carbonyl iron powder and cross-linking agent in step (1) are dried in a drying oven before use, and the drying conditions are 50-80° C. for 8-10 hours.
[0016] In one embodiment of the present invention, the relative molecular mass of the polylactic acid in step (1) is 0.3 to 1.5×10 5 The specifications of carbonyl iron powder are spherical and the particle size distribution is 1 to 3 microns.
[0017] In one embodiment of the present invention, the mass fraction of the carbonyl iron powder in step (1) is 1% to 50%, and the sum of the mass fractions of polylactic acid and carbonyl iron powder is 100%; the mass fraction of carbonyl iron powder is preferably 5% to 40%.
[0018] In one embodiment of the present invention, the cross-linking agent in step (1) is one or both of maleic anhydride and isopropyl tri(dodecylbenzenesulfonyl) titanate.
[0019] In one embodiment of the present invention, the mass fraction of the polylactic acid in step (1) is 50-80%, and the sum of the mass fractions of the polylactic acid and the carbonyl iron powder is 100%, preferably 50%.
[0020] In one embodiment of the present invention, the mass fraction of the cross-linking agent in step (1) is 0.1% to 5%, preferably 0.5% to 3%; the amount of the cross-linking agent added is based on the total mass of the polylactic acid and the carbonyl iron powder.
[0021] In one embodiment of the present invention, the vacuum drying conditions in step (2) are: vacuum degree 0-0.1 MPa, temperature 60°C-90°C.
[0022] In one embodiment of the present invention, the melt spinning temperature in step (3) is 180°C to 210°C, preferably 190°C to 200°C.
[0023] In one embodiment of the present invention, the melt spinning in step (3) is achieved by a twin-screw extruder, and the rotation speed of the twin-screw extruder is controlled to be 20 to 100 r / min.
[0024] In one embodiment of the present invention, the speed of the winding roller in the stretching device in step (3) is 500-1300 r / min.
[0025] The second object of the present invention is to provide a high-stability polylactic acid absorbing fiber prepared by the above method.
[0026] In one embodiment of the present invention, the linear density of the polylactic acid absorbing fiber is 2-4 tex, the breaking strength is 1-3 cN / dtex, and the breaking elongation is 300-100%.
[0027] The third object of the present invention is to provide a polylactic acid absorbing fiber for use in the industrial and civil textile fields.
[0028] Beneficial effects of the present invention:
[0029] (1) The matrix material used in the present invention is polylactic acid, which is a polymer with good biocompatibility and degradability and can be completely degraded into water and carbon dioxide. The absorbing filler used is carbonyl iron powder (CIP), which has good biocompatibility and does not release toxic substances; the spinning of the two can prepare degradable fibers with absorbing properties, thereby achieving the purpose of environmental protection and sustainable development.
[0030] (2) The polylactic acid absorbing fiber prepared by the blending spinning method of the present invention not only has a large amount of absorbing filler coated on the fiber surface, but also has evenly distributed absorbing components inside the fiber. There are covalent cross-linkings between the absorbing particles and the polylactic acid polymer chains, and during use, a stable and lasting absorbing effect can be achieved.
[0031] (3) The ratio of the mass fraction of the absorbing filler to the mass fraction of the polymer in preparing the absorbing fiber of the present invention can be as high as 1:1, and the content of carbonyl iron powder is high, which greatly improves the absorbing performance of the fiber, and the fiber has continuous spinnability.
[0032] (4) The present invention adopts a melt spinning method, has no solvent pollution, has high production efficiency, does not require additional coating equipment during the spinning process, has a simple process, is easy to industrialize, and has certain scalability. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 SEM images of the CIP / PLA fiber surface with different CIP contents; (a) 5wt%; (b) 10wt%; (c) 20wt%; (d) 30wt%; (e) 40wt%; (f) 50wt%;
[0034] Figure 2 SEM images of the cross-section of CIP / PLA fibers with different CIP contents; (a) 5wt%; (b) 10wt%; (c) 20wt%; (d) 30wt%; (e) 40wt%; (f) 50wt%;
[0035] Figure 3 A three-dimensional graph of reflection loss of the CIP / PLA fiber prepared in Example 6;
[0036] Figure 4 It is a two-dimensional graph of reflection loss of the CIP / PLA fiber prepared in Example 6;
[0037] Figure 5 This is a physical picture of the CIP / PLA fiber prepared in Example 6. DETAILED DESCRIPTION
[0038] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0039] The raw material sources involved in the present invention are:
[0040] Polylactic acid granules, Anhui Fengyuan Futailai PLA Co., Ltd., FY801;
[0041] Carbonyl iron powder, Thermo Fisher, 40377, 1-3 micron particle size.
[0042] Example 1
[0043] A method for preparing polylactic acid absorbing fiber (CIP / PLA), the method comprising the following steps:
[0044] The polylactic acid particles, carbonyl iron powder (CIP) and maleic anhydride are dried in a vacuum drying oven at 60°C for 8h, and the polylactic acid particles, carbonyl iron powder and maleic anhydride are weighed by mass, wherein the mass fraction composition is: polylactic acid 95wt%, carbonyl iron powder 5wt%, maleic anhydride 1wt% (the percentage of the total amount of polylactic acid and carbonyl iron powder); the particles are fed into a granulator for uniform mixing, cut into master batches, and the master batches are dried at 0.1MPa and 80°C; the dried master batches are fed into a twin-screw extruder and melt-spun at 195°C: the speed of the twin-screw extruder is controlled to be 40r / min to obtain polylactic acid absorbing fiber precursor; and the polylactic acid fiber precursor is then sequentially subjected to a drawing device for drawing treatment and a collecting device (the collecting device is a collecting roller for collecting the fibers) to obtain the polylactic acid absorbing fiber, wherein the speed of the winding roller in the drawing device is 1100r / min.
[0045] Figure 1 (a) is an electron microscope image of the surface of the prepared polylactic acid absorbing fiber, which shows that polylactic acid and carbonyl iron powder have good compatibility and the fiber surface is smooth.
[0046] Figure 2 (a) is an electron micrograph of the cross section of the prepared polylactic acid absorbing fiber, showing that the carbonyl iron powder is evenly dispersed in the polylactic acid matrix.
[0047] Example 2
[0048] A method for preparing polylactic acid microwave absorbing fiber, the method comprising the following steps:
[0049] Polylactic acid particles, carbonyl iron powder and maleic anhydride are dried in a vacuum drying oven at 60° C. for 8 h, and polylactic acid particles, carbonyl iron powder and maleic anhydride are weighed by mass, wherein the mass fraction composition is: polylactic acid 90wt%, carbonyl iron powder 10wt%, maleic anhydride 1wt% (the percentage of the total amount of polylactic acid and carbonyl iron powder); the particles are fed into a granulator for uniform mixing, cut into master batches, and the master batches are dried at 0.1MPa and 80° C.; the dried master batches are fed into a twin-screw extruder and melt-spun at 195° C.: the speed of the twin-screw extruder is controlled to be 40r / min to obtain polylactic acid absorbing fiber precursor, and then the polylactic acid fiber precursor is sequentially stretched by a stretching device and a collecting device (the collecting device is a collecting roller for collecting the fibers) to obtain polylactic acid absorbing fiber, wherein the speed of the winding roller in the stretching device is 1100r / min.
[0050] Figure 1(b) is an electron microscope image of the surface of the prepared polylactic acid absorbing fiber, which shows that polylactic acid and carbonyl iron powder have good compatibility and the fiber surface is smooth.
[0051] Figure 2 (b) is an electron micrograph of the cross section of the prepared polylactic acid absorbing fiber, showing that the carbonyl iron powder is evenly dispersed in the polylactic acid matrix.
[0052] Example 3
[0053] A method for preparing polylactic acid microwave absorbing fiber, the method comprising the following steps:
[0054] The polylactic acid particles and carbonyl iron powder are dried in a vacuum drying oven at 60° C. for 8 h, and the polylactic acid, carbonyl iron powder and isopropyl tri(dodecylbenzenesulfonyl) titanate are weighed by mass; wherein the mass fraction composition is: 80wt% of polylactic acid, 20wt% of carbonyl iron powder, and 1wt% of isopropyl tri(dodecylbenzenesulfonyl) titanate (the percentage of the total amount of polylactic acid and carbonyl iron powder); the particles are fed into a granulator for uniform mixing, cut into masterbatches, and the masterbatches are dried at 0.1MPa and 80° C.; the dried masterbatches are fed into a twin-screw extruder for melt spinning at 195° C. The speed of the twin-screw extruder is controlled to be 40r / min to obtain polylactic acid absorbing fiber precursor, and then the polylactic acid fiber precursor is sequentially subjected to a drawing device for drawing treatment and a collecting device (the collecting device is a collecting roller for collecting the fibers) to obtain the polylactic acid absorbing fiber, wherein the speed of the winding roller in the drawing device is 1100r / min.
[0055] Example 4
[0056] A method for preparing polylactic acid microwave absorbing fiber, the method comprising the following steps:
[0057] The polylactic acid particles and carbonyl iron powder are dried in a vacuum drying oven at 60° C. for 8 h, and the polylactic acid, carbonyl iron powder and isopropyl tri(dodecylbenzenesulfonyl) titanate are weighed by mass; wherein the mass fraction composition is: 70wt% of polylactic acid, 30wt% of carbonyl iron powder, and 1wt% of isopropyl tri(dodecylbenzenesulfonyl) titanate (the percentage of the total amount of polylactic acid and carbonyl iron powder); the particles are fed into a granulator for uniform mixing, cut into masterbatches, and the masterbatches are dried at 0.1MPa and 80° C.; the dried masterbatches are fed into a twin-screw extruder for melt spinning at 195° C.: the speed of the twin-screw extruder is controlled to be 120r / min to obtain polylactic acid absorbing fiber precursor, and then the polylactic acid fiber precursor is sequentially subjected to a drawing device for drawing treatment and a collecting device (the collecting device is a collecting roller for collecting the fibers) to obtain the polylactic acid absorbing fiber, wherein the speed of the winding roller in the drawing device is 1100r / min.
[0058] Example 5
[0059] A method for preparing polylactic acid microwave absorbing fiber, the method comprising the following steps:
[0060] The polylactic acid particles and carbonyl iron powder are dried in a vacuum drying oven at 60° C. for 8 h, and polylactic acid, carbonyl iron powder and isopropyl tri(dodecylbenzenesulfonyl) titanate are weighed by mass; wherein the mass fraction composition is: 60wt% of polylactic acid, 40wt% of carbonyl iron powder, and 1wt% of isopropyl tri(dodecylbenzenesulfonyl) titanate (the percentage of the total amount of polylactic acid and carbonyl iron powder); the particles are fed into a granulator for uniform mixing, cut into masterbatches, and the masterbatches are dried at 0.1MPa and 80° C.; the dried masterbatches are fed into a twin-screw extruder for melt spinning at 195° C.: the speed of the twin-screw extruder is controlled to be 40r / min to obtain polylactic acid absorbing fiber precursor, and then the polylactic acid fiber precursor is sequentially subjected to a drawing device for drawing treatment and a collecting device (the collecting device is a collecting roller for collecting the fibers) to obtain the polylactic acid absorbing fiber, wherein the speed of the winding roller in the drawing device is 1000r / min.
[0061] Example 6
[0062] A method for preparing polylactic acid microwave absorbing fiber, the method comprising the following steps:
[0063] The polylactic acid particles and carbonyl iron powder are dried in a vacuum drying oven at 60° C. for 8 h, and the polylactic acid, carbonyl iron powder and isopropyl tri(dodecylbenzenesulfonyl) titanate are weighed by mass; wherein the mass fraction composition is: 50wt% of polylactic acid, 50wt% of carbonyl iron powder, and 1wt% of isopropyl tri(dodecylbenzenesulfonyl) titanate (the percentage of the total amount of polylactic acid and carbonyl iron powder); the particles are fed into a granulator for uniform mixing, cut into masterbatches, and the masterbatches are dried at 0.1MPa and 80° C.; the dried masterbatches are fed into a twin-screw extruder for melt spinning at 195° C.: the speed of the twin-screw extruder is controlled to be 40r / min to obtain polylactic acid absorbing fiber precursor, and then the polylactic acid fiber precursor is sequentially subjected to a drawing device for drawing treatment and a collecting device (the collecting device is a collecting roller for collecting the fibers) to obtain the polylactic acid absorbing fiber, wherein the speed of the winding roller in the drawing device is 1000r / min.
[0064] The electromagnetic parameters of the fiber were measured using a vector network analyzer, and the reflection loss (RL) was calculated using the complex dielectric constant and complex magnetic permeability. Figure 3 and Figure 4 The reflection loss of the polylactic acid absorbing fiber can reach 29.4dB within the frequency range of 16 to 18GHz, and the effective absorption bandwidth is 2.5GHz.
[0065] Comparative Example 1
[0066] The only difference from Example 6 is that the carbonyl iron powder is omitted and the addition amount of polylactic acid is adjusted to 100%; other parameters and conditions are the same as those in Example 6.
[0067] The test results show that the prepared polylactic acid fiber does not have microwave absorbing properties.
[0068] Comparative Example 2
[0069] The only difference from Example 6 is that the mass of the carbonyl iron powder is changed, the mass fractions of polylactic acid and carbonyl iron powder are 40wt% polylactic acid and 60wt% carbonyl iron powder respectively, and the other parameters and conditions are the same as those in Example 6.
[0070] The test results show that the prepared polylactic acid absorbing fiber cannot be continuously filamented during the drawing process. This is because when the content of carbonyl iron powder is high, the integrity of the internal segments of polylactic acid PLA is destroyed.
[0071] Comparative Example 3
[0072] The only difference from Example 6 is that the melt spinning temperature is changed to 200° C., and the other parameters and conditions are the same as those in Example 6.
[0073] The test results show that the microwave absorption performance of the prepared polylactic acid is no different from that of Example 6, and the spinning temperature has no obvious effect on the microwave absorption performance of the fiber.
[0074] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing polylactic acid microwave absorbing fiber, characterized in that: The method comprises the following steps: (1) Mixing raw materials: Weigh polylactic acid particles, carbonyl iron powder and cross-linking agent respectively, and mix them evenly according to the proportion; (2) Granulation: The raw materials mixed in step (1) are fed into a granulator, cut into master batches, and the master batches are placed in a vacuum drying oven for drying; (3) Melt spinning: The dried masterbatch obtained in step (2) is fed into a twin-screw extruder for melt spinning, and after being stretched by a stretching device and subjected to a collecting device, the polylactic acid absorbing fiber is obtained.
2. The preparation method according to claim 1, characterized in that: The polylactic acid particles, carbonyl iron powder and cross-linking agent in step (1) are dried in a drying oven before use, and the drying conditions are 50-80° C. for 8-10 hours.
3. The preparation method according to claim 1, characterized in that: The relative molecular mass of the polylactic acid in step (1) is 0.3 to 1.5×10 5 The specifications of carbonyl iron powder are spherical and the particle size distribution is 1 to 3 microns.
4. The preparation method according to claim 1, characterized in that: The mass fraction of the carbonyl iron powder in step (1) is 1% to 50%, and the sum of the mass fractions of polylactic acid and carbonyl iron powder is 100%.
5. The preparation method according to claim 1, characterized in that: The cross-linking agent in step (1) is one or two of maleic anhydride and isopropyl tri(dodecylbenzenesulfonyl) titanate.
6. The preparation method according to claim 1, characterized in that: The mass fraction of the polylactic acid in step (1) is 50-80%, and the sum of the mass fractions of the polylactic acid and the carbonyl iron powder is 100%.
7. The preparation method according to claim 1, characterized in that: The mass fraction of the cross-linking agent in step (1) is 0.1% to 5%; the amount of the cross-linking agent added is based on the total mass of the polylactic acid and the carbonyl iron powder.
8. The preparation method according to claim 1, characterized in that: The melt spinning temperature in step (3) is 180°C to 210°C.
9. The polylactic acid absorbing fiber obtained by the preparation method according to any one of claims 1 to 8.
10. Application of the polylactic acid absorbing fiber according to claim 9 in the field of industrial and civil textiles.
